Analisis Tingkat Kematangan E-Learning Pada Perguruan Tinggi - Darwas, Rahmadini; Rahimullaily, Rahimullaily; Ningsih, Sri Restu; Suryani, Ade Irma (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This study aims to assess the extent to which the e-learning maturity level of Metamedia University is related to data management. Through the COBIT 4.1 framework in the deliver and support domain, namely DS11 (managed data), it can be seen the maturity level of Metamedia University e-learning. This study resulted in a maturity value on the DS11 of 2.82 which means the maturity level is at level 3, namely defined process. In general, it can be explained that the data management process already has standard procedures that have been socialized, but the implementation of these steps is not controlled so that there are many deviations. One of the improvement effort made is the determination of performance indicators and targets that are socialized for each work unit as well as increased training and formal certification of data management personnel. In addition, management optimizes monitoring of data management and performance indicators as well as performance targets.